Lowering the synthesis temperature of high-purity BaTiO3 powders by modifications in the processing conditions - Brzozowski, E. (2003)
In this work, the influence of the BaCO3:TiO2 ratio and milling conditions on the solid-state barium titanate formation at high temperature has been studied. An excess of TiO2 improved the BaTiO3 formation when the TiO2 reactivity was low. Besides, long milling time and an excess of fine grained titanium led to agglomerate formation. In addition, mechanochemical activation performed by rigorous milling and the employment of fine particles of anatase-rich TiO2 powder allowed the reaction to go to completions at temperatures about 150 °C and below than traditionally need.